MECHANISM OF STATE AND SUPRANATIONAL REGULATION IN THE DEVELOPMENT OF ISLAMIC CAPITAL MARKETS (World Economics and Finance Bulletin, 2026)
This scientific paper analyzes the key obstacles to the integration of the national market of the Republic of Uzbekistan into the international market of Islamic securities, using the example of Islamic bonds, namely sukuk. The analysis was based on current global and regional statistical data, standards and research, as well as on the current state of the regulatory framework in the Republic of Uzbekistan. Practical recommendations and development prospects aimed at reducing barriers and increasing attractiveness for international investors were proposed as a solution.
Keywords: Islamic securities market; sovereign sukuk; corporate sukuk